PENINGKATAN PEDALANGAN GAYA BANYUMAS BAGI ANGGOTA PEPADI BANYUMAS - Bagong Pujiono (Abdi Seni, 2019)
PEPADI Purbalingga Regency is one of the organizations of the dalang associations in Purbalingga Regency which is still loyal to the existence of Banyumas-style Pakeliran. Most PEPADI members in Purbalingga Regency learn through self-education so that they need sufficient knowledge concerning Banyumas style of puppetry according to the aesthetic rules of puppetry in general. Therefore, these community service activities aim to improve the quality of Banyumasan puppetry. The training methods used include lectures, appreciation, and demonstrations to describe various styles of puppetry, sabet, catur and various things related to karawitan of puppetry. The results obtained show that Banyumas puppet performance is in accordance to the aesthetic rules of puppetry in general.Keywords: PEPADI, training, wayang performance, Banyumasan styleÂ